2018
DOI: 10.1653/024.101.0406
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Trissolcus japonicus Parasitizing Halyomorpha halys in North American Agriculture

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Coupling crop model and pest models enable IPM Extension staff, farm managers and crop consultants to design and implement economical and ecologically viable strategies to manage invasive pest species, with reduced environmental impacts. Our study also provides a strong foundation for further fundamental studies on pest and natural enemy relationships of H. halys, including its native parasitoid Trissolcus japonicus [82]. Development of crop-pest-parasitoid mechanistic models [83] will be useful to test the implications of various biotic and abiotic factors on tri-trophic dynamics and accompanied variability in biocontrol and crop yield losses in a warming climate for advancing IPM of this invasive insect pest.…”
Section: Discussionmentioning
confidence: 91%
“…Coupling crop model and pest models enable IPM Extension staff, farm managers and crop consultants to design and implement economical and ecologically viable strategies to manage invasive pest species, with reduced environmental impacts. Our study also provides a strong foundation for further fundamental studies on pest and natural enemy relationships of H. halys, including its native parasitoid Trissolcus japonicus [82]. Development of crop-pest-parasitoid mechanistic models [83] will be useful to test the implications of various biotic and abiotic factors on tri-trophic dynamics and accompanied variability in biocontrol and crop yield losses in a warming climate for advancing IPM of this invasive insect pest.…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al [ 10 ] documented the seasonal parasitism of H. halys eggs by T. japonicus in Beijing, China, although its seasonal phenology elsewhere has not been reported. In the USA, it has been detected in woodland [ 6 , 20 , 21 ] and lightly wooded residential habitats [ 13 ], and Herlihy et al [ 6 ] reported that it parasitized significantly more H. halys sentinel eggs in wooded habitats than in soybean or apple plantings. In both the USA [ 20 ] and China [ 10 ], T. japonicus has also been detected in peach orchards.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, it has been detected in woodland [ 6 , 20 , 21 ] and lightly wooded residential habitats [ 13 ], and Herlihy et al [ 6 ] reported that it parasitized significantly more H. halys sentinel eggs in wooded habitats than in soybean or apple plantings. In both the USA [ 20 ] and China [ 10 ], T. japonicus has also been detected in peach orchards. However, there have not been systematic comparisons of T. japonicus detection frequency and relative abundance among the wooded habitats in which it has been found, particularly those adjacent to crops at risk from H. halys attack.…”
Section: Introductionmentioning
confidence: 99%
“…Although Tr. japonicus has been reported mainly from unmanaged landscape habitats, it has also been found in peach orchards (Kaser et al, 2018).…”
Section: Exploration For Natural Enemies In the Native Range And Biolmentioning
confidence: 99%